Determinants of adoption of climate smart agricultural practices among farmers in Bale-Eco Region, Ethiopia - Negera, M.; Alemu, T.; Hagos, Fitsum; Haileslassie, Amare (Elsevier, 2022)
Adoption of climate smart agricultural (CSA) practices has been widely recognized as a promising and successful alternative to minimize the adverse impacts of climate change. However, their adoption among smallholder farmers remains low in developing countries, including Ethiopia. This study examines factors that influence adoption and the level of adoption of multiple CSA practices, including improved agronomy, soil and water conservation, drought tolerant high yielding crop variety, small-scale irrigation, integrated disease, pest, and weed management, and integrated soil fertility management, using survey data from 404 farm households in BaleEco Region (BER), Ethiopia. The study applied a multivariate probit model for analyzing the simultaneous adoptions of multiple CSA practices, and ordered probit model for examining the factors influencing the level of adoption. The CSA practices are found to be complementary. Moreover, farmers' adoption of multiple CSA practices, as well as their intensity of adoption, is significantly influenced by the age of the household head, education, land size, household total asset value, frequency of extension contacts, farmer awareness of climate change, farmer experience with climatic shocks, parcel fertility, slope, and severity of soil erosion. The study's findings suggest that agricultural policy makers and implementers of CSA should recognize the complementarity among CSA practices in order to intensify their adoption among BER farmers and disseminate CSA practices in other parts of the country. Moreover, policymakers should consider household socio-economic, institutional, and parcel-specific factors that positively influence CSA adoption.